Mainstreaming South-South and triangular cooperation: Work in progress at the United Nations - Sebastian Haug (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
South-South cooperation has become an increasingly visible part of international development processes. Together with the expansion of triangular cooperation - that is, cooperation among developing countries supported by a traditional donor or multilateral organisation - the growing clout of South-South schemes reflects shifts in power and wealth towards the former developing world. Against this backdrop, United Nations (UN) entities have repeatedly been asked to mainstream their support for South-South and triangular cooperation (SSTC), but there is hardly any systematic comparative evidence on whether and how they have done so. This paper addresses this gap in three steps. First, it traces the rise and evolution of South-South terminology at the UN, showing that the use of North-South frames had its origins in debates about international inequalities in the 1960s and has expanded in the context of globalisation processes since the 1970s, and also that it is developing countries themselves that have taken up and rallied behind notions of South-South. The paper provides an overview of three partly complementary and partly contradictory approaches that understand South-South cooperation to be a set of technical cooperation modalities; a general political narrative; or a shorthand for inter-state cooperation beyond North-South assistance, with the latter being the dominant de facto understanding among UN entities. Second, the analysis focuses on UN efforts over the last two decades aimed at mainstreaming support for SSTC. It centres around a scorecard of 15 UN entities that maps their level of institutional focus on SSTC, based on insights from strategies, annual reports, publications, monitoring frameworks, budgets and organisational structures. Based on the scorecard, UN entities are grouped under the tentative labels of "champions", "waverers" and "stragglers" for mapping patterns of SSTC mainstreaming. Third, the paper identifies three key factors that, in addition to beliefs in the functional relevance and potential effectiveness of SSTC, have accompanied and conditioned UN mainstreaming efforts. SSTC support has been part of (a) strategic considerations for positioning UN entities in an evolving funding environment; (b) internal bureaucratic dynamics that centre around individuals and shape day-to-day engagement; and (c) geopolitical tensions connected to the increasingly visible fracture between the United States and China. Traditional donors, in particular, tend to approach South-South cooperation as an umbrella for the expansion of China's clout across the UN development system, leading to an intensification of SSTC-related contestations. Overall, support for South-South and triangular cooperation has had a long, multi-faceted, expanding and increasingly controversial trajectory at the UN. With reference to areas of future research and policy recommendations, the paper suggests that UN entities - in coordination with member states - are well advised to expand their efforts for exploring how to best support cooperation that unfolds outside traditional North-South assistance schemes.
Keywords: 330